A replicator-specific binding protein essential for site-specific initiation of DNA replication in mammalian cells - Ya Zhang (Nature Portfolio, 2016)
Origins of mammalian DNA replication are poorly characterised because they lack an Identifiable consensus sequence. Here the authors identify RepID, a protein that binds to a subset of G-rich replication origins and facilitates initiation from those origins.